2012
DOI: 10.1103/physreve.86.056707
|View full text |Cite
|
Sign up to set email alerts
|

Effect of kinetic and configurational thermostats on calculations of the first normal stress coefficient in nonequilibrium molecular dynamics simulations

Abstract: Thermostats for homogeneous nonequilibrium molecular dynamics simulations are usually designed to control the kinetic temperature, but it is now possible control any combination of many different types of temperature, including the configurational and kinetic temperatures and their directional components. It is well known that these temperatures can become unequal in homogeneously thermostatted shearing steady states. The microscopic expressions for these temperatures are all derived from equilibrium distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
(37 reference statements)
1
10
0
Order By: Relevance
“…Calculation of the first normal stress coefficient using their method with EMD simulations is computationally expensive, even with modern computers, because it requires stress autocorrelation function data of extremely high precision. Recently, Daivis [14,22] used the Coleman-Markovitz method to calculate the zero-shear normal stress coefficient of a simple liquid. He also calculated the zero-shear viscosity and first normal stress coefficient using NEMD by extrapolating the shear-rate dependent viscosity and first normal stress coefficient to zero-shear rate, for a range of densities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calculation of the first normal stress coefficient using their method with EMD simulations is computationally expensive, even with modern computers, because it requires stress autocorrelation function data of extremely high precision. Recently, Daivis [14,22] used the Coleman-Markovitz method to calculate the zero-shear normal stress coefficient of a simple liquid. He also calculated the zero-shear viscosity and first normal stress coefficient using NEMD by extrapolating the shear-rate dependent viscosity and first normal stress coefficient to zero-shear rate, for a range of densities.…”
Section: Introductionmentioning
confidence: 99%
“…While the equilibrium and nonequilibrium calculations of the viscosity agreed in the limit of zero-shear rate, the values of the first normal stress coefficient did not. A detailed understanding of this discrepancy is still lacking, but it is clear that the choice of thermostat has a strong influence on the values of nonlinear rheological properties calculated in NEMD simulations [22].…”
Section: Introductionmentioning
confidence: 99%
“…It has also become possible to measure configurational temperatures in systems with discontinuous potentials [28,32], and to employ thermostats that act only on the configurational degrees of freedom [33]; while it is well established that linear transport coe cients (such as viscosity and thermal conductivity) do not depend significantly on the choice of thermostat, it has been shown that nonlinear properties, such as normal stress coe cients, can do [34]. There is no reason a priori that any one temperature should be a better choice than others; in fact, Ayton et al [35] established that in systems experiencing spatially varying strain rates, only Rugh's dynamical temperature is able to correctly account for the resulting heat fluxes.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, reduced density inhomogeneities still form when the thermostat is used to eliminate kinetic temperature inhomogeneities. Therefore, as well as thermal expansion, other factors such as inhomogeneities in the configurational temperature or normal stress differences [36], must be involved in the relationship between the temperature and density profiles. Figure 2 shows the velocity, density and temperature profiles for the set of system 1 simulations summarized in Table I.…”
Section: A Stf Only: Long Wavelength Density Perturbationsmentioning
confidence: 99%